Mediating Effect of Personal Meaning in the Prediction of Life Satisfaction and Mental Health Problems Based on Coronavirus Suffering - Arslan, Gökmen; Yıldırım, Murat; Leung, Mega M. (Frontiers in Psychology, 2021)
The onset of the COVID-19 pandemic has triggered a multi-faceted crisis worldwide. Researchers and health authorities in various parts of the world echoed the dire condition of the public’s mental health. This study sought to examine the mediating effect of personal meaning on the association between coronavirus (COVID-19) related suffering, mental health problems, and life satisfaction. Participants included 231 adults (mean age = 46.65±13.98; 68% female) and completed measures of suffering related to COVID-19, meaning, life satisfaction, and mental health problems online. Findings from mediation analysis showed that suffering had significant associations with personal meaning, mental health, and well-being. Furthermore, the personal meaning was significantly associated with adults’ mental health and well-being and mediated the negative effect of suffering on mental health and well-being. Overall, results from this study indicate that personal meaning is an important promotive factor that may help to understand the negative effect of coronavirus related suffering on mental health and well-being amid the public health crisis.